THE MINIMUM NUMBER OF VALVES FOR DIATOMS IDENTIFICATION IN RAWAPENING LAKE, CENTRAL JAVA - Tri Retnaningsih Soeprobowati; S. Djalal Tandjung; Sutikno Sutikno; Suwarno Hadisusanto; Peter Gell (BIOTROPIA, 2016)
Technical challenges in using diatoms for paleolimnological studies include the identification and enumeration of diatom valves. The minimum number of valves required for identification varies, ranging from 100 to 700 valves of the dominant species. This task can be very time-consuming, particularly when diatom valves are scarce. This study was conducted to determine the minimum number of valves needed for identification in diatom assemblages from Rawapening Lake, Central Java, Indonesia. Based on 314 samples collected from Rawapening Lake, diatom counting efficiency exceeded 0.85 when a minimum of 300 valves was counted. The number of diatom species identified remained stable after counting at least 300 valves. Therefore, the minimum number of diatom valves required to represent the assemblage for paleolimnological analysis is 300.